Icing simulation and ice pattern formation based on a phase-field method - Wang, Zhihua (2025)
A phase-field model for three-phase flows with cylindrical/spherical interfaces is established by combining the Navier-Stokes (NS), the continuity, and the energy equations, with an explicit form of curvature-dependent modified Allen-Cahn (AC) and Cahn-Hilliard (CH) equations. These modified equations are proposed to solve the inconsistency of the phase-field method between flat and curved interfaces, which can result in “phase-vanishing” problems and the break of mass conservation during the phase-changing process. It is proved that the proposed model satisfies the energy dissipation law (energy stability).